Strategies for Preserving Local Wisdom in Islam and Its Implementation in Indonesia - Panggih Widodo; Hamzah Hamzah (State Islamic Institute of Palopo, 2024)
This study discusses Islamic strategies for preserving local wisdom and the implementation of these strategies in Indonesia with the type of literature research involving primary and secondary data. The approaches used are normative theological approaches, Islamic law, and anthropology. The data in this study was processed with qualitative descriptive techniques and content analysis. This paper explains that Islam has its strategy to preserve local wisdom. That is by taking a certain form of local wisdom as Islamic law, encouraging the implementation of local wisdom forms that contain good values, and giving a touch of Islam to various existing local wisdom. This strategy was also applied by Islamic scholars in Indonesia in dealing with a pluralistic Indonesian society full of various forms of wisdom that were firmly held by the community. The urgency of this paper is that it can provide an overview of the strategies applied by Islam to preserve local wisdom in Muslim communities, including in Indonesia. In addition, it can also be used as a guideline as a strategy to deal with various new customs and cultures that arise with the times, so that they are by Islamic teachings.